Ответ:
Пошаговое объяснение:
а) -2/3+2/1-4/6-3/1 приводим все к общему знаменателю 6
-4/6+12/6-4/6-18/6=-14/6=-2 1/3
б)3/8-2/1-7/16+8/1 приводим все к общему знаменателю 16
6/16-32/16-7/16+128/16=95/16=5 15/16
в)-4/1+7/8-3/4+9/1 приводим все к общему знаменателю 8
-32/8+7/8-6/8+72/8=41/8=5 1/8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
а) -2/3+2/1-4/6-3/1 приводим все к общему знаменателю 6
-4/6+12/6-4/6-18/6=-14/6=-2 1/3
б)3/8-2/1-7/16+8/1 приводим все к общему знаменателю 16
6/16-32/16-7/16+128/16=95/16=5 15/16
в)-4/1+7/8-3/4+9/1 приводим все к общему знаменателю 8
-32/8+7/8-6/8+72/8=41/8=5 1/8